Kajian Hukum Lingkungan Atas Transisi Mobil Berbahan Bensin Ke Listrik Terhadap Penggunaan Litium dan Limbah Baterai - Saputra, Muhammad Dewanto Adi (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This study critically examines Indonesia's environmental law regulations governing the transition from gasoline to electric vehicles, which relies on water- and energy-intensive lithium extraction—up to 22.729 galon per ton of carbonate and 13,92 ton CO₂ ekuivalen from hard rock mining—alongside the explosion of toxic B3 battery waste, revealing the paradox of tailpipe emission reductions offset by upstream externalities such as hydrological degradation and heavy metal contamination akin to the Teluk Buyat case, where UU 32/2009 PPLH and Perpres 79/2023 fail to mandate holistic life cycle management. Employing a doctrinal normative juridical approach supplemented by empirical elements through industry interviews, the analysis confirms normative fragmentation in instruments like PP 27/2020 limbah B3 and Permen LHK 12/2021 emisi daur ulang, which inadequately address EPR tracking and 95 percent recovery rates per battery chemistry (NMC-LFP), amid implementation challenges of Perpres 79/2023 including local recycling capacity at only 10 percent, weak inter-ministerial coordination, and the transfer of imported lithium impacts from Chile-Australia violating the precautionary principle and polluter pays doctrine. In conclusion, this fragmented normative framework threatens NZE 2060 via risks of lithium leaching and tropical thermal runaway, necessitating reforms such as a dedicated EPR mandatory act, national task force, and RD in hydrometallurgy to synergize green constitutionalism with resource sovereignty.